Dampak Project-Based Learning terhadap Keterampilan Berpikir Kritis Siswa SMA: Meta-Analisis dalam Konteks Pembelajaran Biologi di Indonesia - Harmoko; Nur Hayati (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
This study is motivated by the low level of senior high school students’ critical thinking skills in Biology learning in Indonesia and the urgent need for instructional innovations that effectively foster higher-order thinking skills. The primary research problem lies in the inconsistency of findings from previous studies regarding the effectiveness of Project-Based Learning, thus necessitating a comprehensive analysis to obtain more robust and integrated conclusions. The study aims to examine the effect of Project-Based Learning on students’ critical thinking skills and to identify moderating factors influencing this effect through a meta-analysis of 27 relevant studies. The results indicate that Project-Based Learning has a significant impact, with a cumulative effect size of 0.98, categorized as large and consistent, supported by low heterogeneity (I² = 18.70%) and strong resistance to publication bias. The findings further reveal that critical thinking indicators serve as the most dominant moderating factor, while sample size and additional variables do not show significant influence, and the standalone model demonstrates slightly higher effectiveness than combined approaches. The conclusion affirms that Project-Based Learning is effective in enhancing critical thinking skills through contextual, active, and student-centered learning. The novelty of this study lies in the systematic integration of multiple studies through meta-analysis, producing strong empirical evidence, as well as the comprehensive identification of moderating factors that have been rarely explored, thereby contributing both theoretically and practically to evidence-based Biology education development.